Kepemimpinan Entrepreneurial Berbasis Keterampilan pada Ekonomi Berkembang - Richa Nahdalaily Fathara; Margo Purnomo; Erna Maulina (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The purpose of this study was to examine entrepreneurial leadership and determine the skills essential for entrepreneurial leadership in achieving success in a growing economic environment. The focus of this research specifically focuses on the entrepreneurial leadership found in the culinary sector in Pekanbaru. This study identified categories of entrepreneurial skills, business technical skills, interpersonal skills, conceptual skills, and entrepreneurial skills. The results of this study in terms of theory will provide a clear picture of entrepreneurial leadership that can be used as a reference in making skills-based empirical models based on phenomena in developing economies. Meanwhile, in terms of practice, this research is also useful as a reference for practitioners and policy makers about the skills and factors needed by leaders in achieving success as entrepreneurial leadership. Keywords : Skills, Leadership, Developing Economy, Entrepreneurial Leadership, Indonesian Entrepreneurship